2014
DOI: 10.17305/bjbms.2014.4.205
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic alterations of the Wnt signaling pathway in cancer: a mini review

Abstract: Epigenetic mechanisms play a crucial role in cellular proliferation, migration and differentiation in both normal and neoplastic development. One of the key signaling pathways whose components are altered through the epigenetic mechanisms is the Wnt signaling pathway. In this review, we briefly discuss the key concepts of epigenetics and focus on the recent advances in the Wnt signaling pathway research and its potential diagnostic and therapeutic implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 34 publications
(38 reference statements)
0
26
0
Order By: Relevance
“…Deregulated Wnt/ β -catenin signaling with cancers has been well documented in tumor initiation, progression, and metastasis, including lung cancer [1820, 51, 52]. Blocking β -catenin signaling for cancer treatment has thus generated significant interests [53].…”
Section: Discussionmentioning
confidence: 99%
“…Deregulated Wnt/ β -catenin signaling with cancers has been well documented in tumor initiation, progression, and metastasis, including lung cancer [1820, 51, 52]. Blocking β -catenin signaling for cancer treatment has thus generated significant interests [53].…”
Section: Discussionmentioning
confidence: 99%
“…Cancer cell invasion leading to metastasis is also evident in the case of class 1 HDACs, since these are responsible for regulating E-cadherin, where the loss of E-cadherin results in the loss of cell adhesion, ultimately influencing metastasis progression [129]. Epigenetic inactivation of the inhibitors of the Wnt/β-catenin signaling cascade has also been reported to contribute to tumor metastasis [130]. In addition, studies on human cancer have shown that the hypermethylation of the promoters of Wnt antagonists, such as SFRP and DKK3, contribute to their dysregulation [131,132].…”
Section: Epigenetic Contributionmentioning
confidence: 99%
“…The GO term enrichment analysis and pathway analysis were carried out on the differentially expressed genes mentioned above, and we found that siRNA‐mediated knockdown of dbpA might regulate the expressions of tumor‐related genes through altering the biology process of SW620 cells such as signal transduction (Shimizu and Nakagawa, ), transport (Cautain et al, ), cell development (Akhtar Ali et al, ), response to stress (Pettersen et al, ), and regulation of apoptosis (Moon et al, ), which have been reported to participate in numerous types of tumors development. KEGG pathway analysis further identified that eight KEGG pathways “MAPK signaling pathway” (Lei et al, ), “Pathways in cancer” (Hein et al, ), “Chemokine signaling pathway” (Chow and Luster, ), “NOD like receptor signaling pathway” (Zaki et al, ), “Focal adhesion” (Lee et al, ) “Basal cell carcinoma” (So et al, ), and “Wnt signaling pathway” (Serman et al, ) related to tumorigenesis were significantly changed in siRNA‐dbpA group, which might be implied by that dbpA played an import role in CRC development.…”
Section: Discussionmentioning
confidence: 99%